PELESTARIAN KEPERCAYAAN MARAPU DALAM MASYARAKAT DI SUMBA BARAT - Suarjaya, I Wayan (Widya Sandhi, 2019)
This study aims to examine the preservation of merapu local wisdom carried out by the community in West Sumba. This research was designed in the type of qualitative descriptive research by focusing on case studies on the implementation of the noble traditions of Hindu Nusantara supporters. Based on the results of the study it was found that there were several traditions carried out in order to preserve the local wisdom of merapu. First, the implementation of cultural traditions carried out in everyday life that involve aspects of trust, such as in marriage ceremonies. Second, mutual assistance activities in order to build houses and look for building materials in the forest. Third, activities related to the livelihood system, such as in agriculture. Activities began to open or begin to go down to the rice fields and harvest activities together in the fields that they did in mutual cooperation. Fourth, the implementation of the ritual welcomes the presence of worm season in the sea or beach called Nyale associated with the preparation of going down to the rice fields. In that month it has become a tradition that people who adhere to the Marapu belief spill down to the beach accompanied by rituals welcoming thousands of worms. Fifth, a joint program in the form of warring horsemen called Pasola which is held annually by involving many people, both the committee, the perpetrators and the audience